IMMOBILIZATION OF MAGNETIC BEADS FOR MICROFLUIDIC IMMUNOASSAYS - NGUYEN THANH QUA; Kim Jeongyun; Dae woong Lee; Choi Ji Seob; Park Jae ho; Jeon, Hojeong; 박우태; Lee Sang Youp (PROCEEDINGS OF THE ASME/JSME/KSME JOINT FLUIDS ENGINEERING CONFERENCE, 2019, VOL 4, 2019)
Employing magnetic beads (MBs) to microfluidic chips has enabled diverse microscale biomedical applications involving isolation of target molecules, such as, separation, and biosensing. In this report a microfluidic immunoassay chip that can temporarily immobilize MBs for the detection of target biomarkers within a sample solution flown through its channels is introduced. A through-hole structure of the MB capture zone and valves that can control the direction of the flow enabled immobilization of MBs with high reproducibility. Controlling immobilization of MBs shows promise for reproducible immunoassay signal detections for the same concentration of biomarker which is crucial for quantification of the assay. In addition, the structure and position of the captured MBs can potentially be optimal for immunoassay performances where immunoassay reagents including the antigen and the detection antibody are flown through the MB captured through hole maximizing contact for high binding efficiencies.